Genotoxic and antigenotoxic properties of selenium compounds in the in vitro micronucleus assay with human whole blood lymphocytes and tk6 lymphoblastoid cells - Eduard Cemeli; Ricard Marcos; Diana Anderson (The Scientific World Journal)
Selenium is known to possess both genotoxic and antigenotoxic properties. In the present study, we have evaluated the genotoxicity and antigenotoxicity of three selenium compounds (sodium selenate, sodium selenite and selenous acid) by measuring in vitro micronucleus induction. Assays were conducted in whole blood lymphocytes and in the TK6 lymphoblastoid cell line, with and without co-treatment with potassium dichromate, a known genotoxic compound. In general, the compounds were more active in TK6 cells than they were in blood lymphocytes. Only 1 μM selenous acid increased the frequency of binucleated cells containing micronuclei (BNMN) in blood lymphocytes, while all three selenium compounds increased BNMN in TK6 cells. In addition, combinations of selenous acid and potassium dichromate resulted in lower frequencies of BNMN than potassium dichromate alone in blood lymphocytes, while combinations of sodium selenate and potassium dichromate produced lower frequencies of BNMN than potassium dichromate alone in TK6 cells. The concentrations of selenium compounds that were used, in combination with the medium components and the biological physiology of the whole blood lymphocytes and TK6 cells, could have affected the redox potential of the compounds, switching the chemicals from a pro-oxidant to antioxidant status and vice-versa. The lower activities of the compounds in blood lymphocytes may be due to the protective effects of blood components. The results indicate that the genotoxic and antigenotoxic properties of selenium compounds are highly dependent upon the conditions under which they are evaluated.